PERTUMBUHAN LINGKARAN POHON JATI PADA DUA SISTEM KULTUR BERBEDA DI JAWA TIMUR - Iriwi Louisa S. Sinon (FMIPA Universitas Papua, 2007)
Study dendrochronology or tree-ring dating is defined as the study of chronological sequence of annual growth rings in trees. Teak (Tectona grandis) is one of various tree species that has been identified for the use of tree-ring studies in tropical regions. Teak is found to be suitable for dendrochronology as it is long-lived and develops defined annual growth rings. In Java, teak cans growth naturally or intensively in plantation. The two silviculture conditions will give different sensitivity on climate effect. Therefore, the effect of silviculturer will on natural teak and plantation teak in Saradan, Madiun, and East Java. As a part of the study, ten core samples from natural- growth teak were measured. The samples of growth rings is spanned from 1832 – 2004. Using the COFECHA program, the correlation of the samples (r) was found to be 0.44 point, which is satisfactory to the standard used in dendrochronology. Thus, from this study it can be concluded that natural teak could still be used in dendrochronology, although the sensitivity are not as high as plantation teak.